Detection of an unknown fusion protein in confiscated black market products. Issue 11 (14th September 2014) - Walpurgis, Katja; Krug, Oliver; Thomas, Andreas; Laussmann, Tim; Schänzer, Wilhelm; Thevis, Mario
<x xml:space="preserve">Abstract</x> Even without clinical approval, many performance‐enhancing drugs are available on the black market and can therefore be easily obtained by cheating athletes. The misuse of these preparations can be associated with unforeseeable health risks – either due to a poor quality of the drugs or as a result of an insufficient clinical assessment. Moreover, confiscated black market products have frequently been shown to contain ingredients other than those declared on the label as well as additional by‐products or compounds with a modified molecular structure. This communication describes the identification of an unknown fusion protein observed in several unlabelled black market products obtained from independent sources. Sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS‐PAGE) and liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) analysis of the confiscated preparations indicated the presence of an 18‐kDa fusion protein consisting of the bacterial redox protein thioredoxin‐1 (Trx, 12 kDa) and a 6‐kDa peptide of unassigned composition. Trx has no relevance as performance enhancing agent but is routinely used as solubility tag for recombinant protein production. Further evaluation of the acquired MS/MS data revealed both an additional His tag and a thrombin cleavage site between the tags and the presumed bioactive peptide. However, thrombin cleavage of the fusion protein and LC‐MS/MS analysis of the resulting peptide fragment finally suggested that the unknown protein is only the product of an empty expression vector without the DNA insert of interest. These findings are a further alarming example for the high level of risk that athletes take when misusing drugs obtained from the black market. Copyright © 2014 John Wiley & Sons, Ltd.